Effect of liming on upland rice, common bean, corn, and soybean production in cerrado soil - Fageria, Nand Kumar (Pesquisa Agropecuaria Brasileira, 2001)
Liming is one of the most efficient cultural practice to improve crop yields in acid soils, but there are a few data about liming in rotation system of annual crops. A field experiment was conducted for four consecutive years with the objective to determine adequate level of lime for upland rice (Oryza sativa L.), common bean (Phaseolus vulgaris L.), corn (Zea mays L.), and soybean (Glycine max [L.] Merr.) grown in rotation on a Dark-Red Latosol. Treatments arranged in a complete block design, with three replications, were the following lime rates: 0, 4, 8, 12, 16, and 20 ton ha-1. Grain yields of common bean, corn, and soybean were significantly increased with liming. However, upland rice yield was not affected. The 90% maximum yield considered as economic level was obtained with the application of 5, 8 and 9 ton ha-1 lime on common bean, corn and soybean respectively. Soil pH, exchangeable Ca and Mg, Ca/K and Ca/Mg ratio, Ca saturation and Mg saturation increased significantly with lime aplication at 0-20 and 20-40 cm soil depth.